Analisis Ajaran Syiah Itsna Asyariah Pokok-Pokok Ajarannya Dan Dampaknya Terhadap Keberagaman Islam Di Indonesia - Lintang Ardiansyah; Nur Eliyah; Afifah Sahlah; Lutviya Zahira Shofa; Muhammad Alwan Fathurrobbanie; Muhamad Parhan (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Syiah is one of the sects of Islamic theology whose existence is a necessity. Since its emergence and development has sparked much debate. And at this time the treatment of Syia has led to a form of violation of the principle of freedom of religion, but it is not without reason because the understanding and practice of religion is very different from the practices that have developed in the world, especially Indonesia, even leading to heresy. In Syia there are also many schools in it. One of them is Shia 'Itsna 'Ashariah. The research uses a literature study method by analyzing literature from books and journals related to Shia. The purpose of this research is to examine Shia 'Itsna 'Assariah, its main teachings, from its emergence and development in Indonesia to its impact on Islamic diversity in Indonesia.